The Effect of Work Environment, Commitment, and Discipline on Employee Performance - Elisabeth, Cherly (Manunggal Halim Jaya, 2022)
This study is to Influence the Work Environment, Commitment, and Discipline on Employee Performance at PT. Bank Rakyat Indonesia (Persero) TBK Makassar Region Internal Audit. The total population in this study were all employees of PT. Bank Rakyat Indonesia (Persero) TBK Audit, totaling 50 people. The number of samples in this study is relatively small, so the sample used in this study is the entire population of 50 people. This research was conducted using a survey approach, the type of research conducted was descriptive quantitative. Data collection was carried out using questionnaires, literature, and observation. Data analysis used descriptive and inferential statistics (multiple linear regression). The results of this study indicate that simultaneously the work environment variables, commitment, and discipline have a significant effect on employee performance at PT. Bank Rakyat Indonesia (Persero) TBK Makassar Region Internal Audit. Partially the work environment variables, commitment, and discipline have a significant effect on employee performance at PT. Bank Rakyat Indonesia (Persero) TBK Makassar Region Internal Audit